Verses and Surahs of the Qur'an and the Problems of Determining the Tartib of Surahs and Verses of the Qur'an - Cepty Affifah Ranty; Lia Nur ‘Aini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Qur'an is guidance and guidance for humans. The Al-Qur'an as a guide does not provide maximum function if it is not practiced. The practice of its contents cannot run well when the contents of the Al-Qur'an are not understood. To understand its contents, it is necessary to study its contents. Studying the contents of the Al-Qur'an of course requires a tool in the form of Al-Qur'an sciences which are used to study interpretations in order to understand its contents, namely regarding the order of the verses and surahs of the Al-Qur'an. This research uses a bibliographic research approach, to collect various literacy sources as the main material for the study. The order of verses and surahs of the Qur'an that the author means is a discussion regarding the placement of verses and surahs contained in the manuscripts of the Qur'an. There is no disagreement between scholars regarding the etiquette of Al-Qur'an verses. The scholars agree that it is something that is tauqifi, that is, it is a guidance from the Prophet Muhammad. As for the order of the surahs of the Qur'an, there are differences of opinion among the scholars. Among them, they state that the order of the suras of the Qur'an is tauqifi, among them they also state ijtihadi and the final opinion is that some of the surahs of the Qur'an are tauqifi and some are ijtihadi.